Audit Tenure and Auditor Reputation on the Going Concern Audit Opinion of Firms on the Indonesian Stock Exchange: Does Audit Quality Mediate? - Nur’Illiyyien Nur’Illiyyien; Neks Triani; Kartini Kartini; Sri Sundari (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to investigate the impact of auditor reputation and audit duration on ongoing concern audit opinions through audit quality. The research sample consists of 17 manufacturing companies published between 2020 and 2024 on the Indonesia Stock Exchange (IDX). Logistic regression was used to analyze the data with the aid of of Smart Partial Least Square (SmartPLS) software. Based on the results of hypothesis testing, audit tenure has no effect on the issuance of a going concern audit opinion. On the other hand, auditor reputation has been proven to influence both the going concern audit opinion and the quality of the audit itself. However, audit quality does not affect the going concern audit opinion, nor does it mediate the relationship between audit tenure and auditor reputation on the opinion.